2010
DOI: 10.3109/10641960903265220
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uric Acid with Risk Factors for Chronic Kidney Disease and Metabolic Syndrome in Patients with Essential Hypertension

Abstract: Hyperuricemia has recently been recognized to not only be a predictor of cardiovascular disease but also a marker of metabolic syndrome. We examined the association between uric acid levels and various clinical parameters, including the components of metabolic syndrome, in essential hypertension. One hundred forty-six untreated Japanese hypertensive patients (mean 58.3 years) without overt cardiovascular disease were divided into low and high uric acid groups by the median uric acid value (cut-off: 6.3 for men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These studies have been mainly conducted on healthy Asiatic population. Nevertheless, the results are consistent with those from smaller studies conducted in North or South America (135,136,145) or on diabetic (140,141) and hypertensive patients (138).…”
Section: Uric Acid: a Renal Biomarker For Mets?supporting
confidence: 88%
“…These studies have been mainly conducted on healthy Asiatic population. Nevertheless, the results are consistent with those from smaller studies conducted in North or South America (135,136,145) or on diabetic (140,141) and hypertensive patients (138).…”
Section: Uric Acid: a Renal Biomarker For Mets?supporting
confidence: 88%
“…Different studies have identified an association between hyperuricemia and a moderate increase in glucose concentrations, IR, hyperinsulinemia, creatinine, early kidney damage, obesity, type 2 diabetes, and CVD . These data are very interesting because treatment with Diamel from 6 months onwards simultaneously improves insulin and UA concentrations, in addition to IR and IS.…”
Section: Discussionmentioning
confidence: 89%
“…It is unclear whether alcohol itself and alcohol-induced hypertension cause hypertrophy or the coexistence of hyperuricemia exacerbates cardiac remodeling. We have previously reported that the uric acid level is positively correlated with LV wall thickness in untreated hypertensive patients including drinkers and non-drinkers [38]. In another study, there was also a positive relationship between the uric acid level and LVMI in hypertensive patients including both drinkers and non-drinkers [39], and in males of the Japanese general population [40].…”
Section: Uric Acid and Hypertrophymentioning
confidence: 85%